Political Scandal and Public Figure - Arum Sekar Cendani; Pulung Setiosuci Perbawani (PCD Journal, 2020)
Indonesian society is familiar with the terms 'public figures' and 'celebrities', but the distinction is often not understood properly. The public's interest in content that focuses on entertainment, lifestyles, and gossip, as well as the presence of a media that facilitates such content, makes the process of 'celebrating' common. This process has resulted in the private space of public figures being transformed into objects of public consumption.Scandals are often quite popularly discussed among the public, especially when their subject is a public figure. However, studies of how scandals affect the public and its political behaviour have not been widely documented. In 2018, Indonesian news media began widely covering the divorce of well-known politician Basuki Tjahaja Purnama (BTP/Ahok) from his ex-wife Veronica Tan, and this brought questions of extramarital affairs to the surface in the midst of a heated local election atmosphere. This situation was divisive, and received various public responses. Previous studies have shown that scandals tend to negatively affect popular attitudes towards the politicians involved in them. In Indonesia, scandals have been common, widely recognised by the public, but their effects are never discussed in depth. Therefore, this study, which involved around 400 respondents, seeks to provide an overview of how the Indonesian public responds to politicians involved in scandals and how such scandals affect politicians' electability. The results of this study show that scandals do affect the public's political attitude, but not in the ways suggested by existing studies.